Development of a universal bidirectional galvanic isolated switch module for power converter applications - Mokhalodi, Kopano (My University, 2013)
The global trends towards energy efficiency have facilitated the need for technological advancements in the design and control of power electronic converters for energy processing. The proposed design is intended to make the practical implementation of converters easier. The development of a universal bidirectional galvanic isolated switch module will be used to drive any MOSFET or IGBT in any position in any topology whether the load is AC or DC. Semiconductor switches are required and are also integrated for fast switching times in power converter applications The structure of the power switch module consists of an opto-coupler which will provide an isolation barrier for maximum galvanic isolation between the control circuitry and power stage. It also consists of a high performance gate drive circuit for high speed switching applications with a floating supply.
M. Tech. (Engineering: Electrical, Department Electronic Engineering, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: Power electronic converters; Energy processing; Electric converters; Universal bidirectional galvanic isolated switch module; MOSFET; IGBT; Power switch; Switching applications; 621.317; Electric current converters.; Electric switchgear